SURVEI PENGGUNAAN FORMALIN DAN BORAKS PADA PEDAGANG BAKSO TUSUK DI SEKOLAH DASAR KECAMATAN WENANG DAN KECAMATAN MALALAYANG - Pricilya A.M. Kaligis; Ir. Tineke M. Langi, MSi; Ir. Thelma D.J. Tuju, MSi. (COCOS, 2017)
ABSTRACTThe purpose of this study to analyze content of formaldehyde and borax in meatballs skewers sold by vendors in elementary school (SD) in the district and sub-district Wenang Malalayang. This study uses a survey of merchant / seller meatball skewers in elementary school (SD) and the District Subdistrict Wenang Malalayang about the use of formaldehyde and borax. The results showed that not found the use of borax and formaldehyde in the meatball skewers are sold in 29 schools in the district and sub-district Wenang Malalayang Manado.Keyword : survey of traders meatball skewers, formaldehyde and borax